Pengaruh Pemberian Makanan Tambahan Pemulihan Pada Balita Gizi Kurang Terhadap Perubahan Status Gizi Di Wilayah Puskesmas Kramat Kabupaten Tegal - Septiani, Septiani; Sunarto, Sunarto (Poltekkes Kemenkes Semarang, 2014)
Background : The toddler is one of the population groups that are vulnerable to nutritional problems. They are experiencing rapid growth and development in this period of time and thus require the supply of food and nutrition in sufficient quantities and adequate. Malnutrition in infancy can lead to impaired growth and development of the physical, mental, social, intellectual nature persist and continue to be carried into adulthood.Objective : The purpose of this study was to determine the effect of supplemental feeding on infant malnutrition recovery to changes in nutritional status in the Puskesmas Kramat Tegal regency.Method : Research in using this type of analytical research, research design used in this study was a cohort study conducted in the design of non randomisassi. The research sample was 23 children who received food supplement to recovery and 23 infants who were not given food supplement to recovery that will be the control group. Analysis researchers used statistical tests to analyze the effect of food supplement recovery to changes in nutritional status using test Anacova Repeated Meansure with Î± 0.05.Results : The results showed that there was the influence of supplementary feeding on infant malnutrition recovery to changes in nutritional status (p value 0.012).Conclusion : The conclusion of this research is the nutritional status of the comparator group average Z score before -2.426, month-1 is -2.052, month-2 is -2.157 and -2.783 3rd month. The nutritional status nutritional status prior to treatment groups treatment was -2.504, -2.222 month 1, month 2 is -1.190 and three months to an average z score to -1.280. The author expects for the health department in order to improve the efficiency of the implemented processes packets food supplement to recovery. Food supplement to recovery mentoring program so that a given package is really right on target and acceptable to children under five goals.